Pengaruh luas panen, produktivitas dan harga tanaman tebu terhadap kesejahteraan hidup petani tebu di Indonesia - Purnomo, Didit; Savikri, Nando (Nur Science Institute, 2021)
The agricultural sector is one of the most important and strategic sectors for the economy in Indonesia. One of the indicators/measurements that can be used to assess farmer welfare is the Farmer's Exchange Rate. The purpose of this study was to determine the effect of harvested area, productivity and price of sugarcane on the welfare of farmers. The data used in this study are secondary data obtained from Statistics Indonesia (BPS) and PUSDATIN. The data analysis method used to determine the effect of harvested area, productivity, and sugarcane prices on the exchange rate of sugarcane farmers is regression analysis using the Ordinary Least Square method. This study found that the productivity variable harmed the welfare of sugarcane farmers for the period 2000-2017. At the same time, the variables of the harvested area and sugarcane prices positively affect the welfare of sugarcane farmers (NTP).